Narrative apologetics : sharing the relevance, joy, and wonder of the Christian faith - McGrath, Alister E., 1953- (Grand Rapids, Michigan : Baker Books, 2019)
"One of the world's leading Christian apologists delivers a groundbreaking book that shows how the Christian story can be told and retold to connect effectively with unbelievers in today's post-Christian culture"--
Introducing narrative apologetics -- The theological foundations of narrative apologetics -- The practical application of narrative apologetics -- Biblical narratives : opening windows of perception -- Strategies and criteria for narrative apologetics -- The Christian story and the meaning of life -- Handing over : developing narrative approaches to apologetics.
Includes bibliographical references.
Keywords: Apologetics -- Study and teaching; Narration (Rhetoric); Storytelling -- Religious aspects -- Christianity